Use of Media Video Learning in Increasing Student Interst in Learning on Civic Education Subjects in SMAN 8 Serang City - Agustin, Fhanisa; Ayu Puspita, Diah; Hafidin, Hafidin (LPPM Universitas Primagraha, 2022)
The modern technology that develops today in the field of communication with products such as hardware and software equipment presented today has affected the entire sector including in the education sector. The use of communication technologies for educational activities, educational technologies, as well as educational media is necessary in order to learn to teach. Education is an urgent need in the future. Technological development is one of the media that is based on video learning as a tool that helps in the delivery of materials or references used by teachers or students. The aim of this study is to know the influence of video learning media in increasing student interest in SMAN 8 Serang City. This research uses qualitative research methods with a descriptive approach. This study is a field research. (field research). Research results show that learning using video learning media has a significant impact on student learning interests.